PERANCANGAN PONDOK PESANTREN MODERN DI KECAMATAN BALEREJO DI KOTA MADIUN JAWA TIMUR - Dandy Irfansyah; Inggit Musdinar Sayekti Sihing Yang Mawantu; Karya Subagya (MAESTRO, 2023)
ABSTRACT Islamic boarding schools as the forerunner of the Islamic education system in Indonesia with the style and character of indigenous people in instilling the ideology of education in Indonesia. Islamic boarding schools with all their uniqueness are still expected to support the development of the education system in Indonesia. The originality and uniqueness of pesantren aside from being a treasure of the nation's cultural traditions is also a supporting force for the pillars of education to emerge moral national leaders. Therefore, with the realization of modern Islamic boarding schools that can meet all the needs of prospective students in an effort to improve the learning system by prioritizing the main facilities that are in accordance with the general school curriculum and supporting Islamic boarding schools, especially paying attention to comfort and safety by applying modern architectural concepts, so that people's trust Parents of students continue to increase to Islamic boarding schools.